Non-trading behaviour in choice experiments - Michael Ahlheim; Jan Neidhardt (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
This paper addresses a methodological problem of choice experiments, namely the problem that respondents sometimes avoid the intellectual effort of thoroughly considering the trade-offs between different alternatives that are the essence of every choice experiment, and tick instead the next best alternative without the necessary deliberation. This kind of behaviour which is called "nontrading" in the respective literature calls into question the validity of choice experiments. In this paper, which is based on an online choice experiment concerned with consumer's tastes for table grapes with 1,000 participants, we suggest possibilities to identify potential non-traders not only by their answering behaviour but also by some general characteristics we found to be typical of this kind of respondent.
urn:nbn:de:bsz:100-opus-11885
Keywords: 330; Non-Trading Behaviour; Discrete Choice Experiment; Table Grapes